2022
DOI: 10.21203/rs.3.rs-2273657/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serial Viral Load Analysis by Ddpcr to Evaluate Fnc Efficacy and Safety in the Treatment of Moderate Cases of Covid-19

Abstract: A highly pathogenic coronavirus termed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in 2019 causing coronavirus disease 2019 (COVID-19). Trials have been carried out to find drugs effective in fighting the disease, as COVID-19 is being considered a treatable disease only after we have antivirals. A clinical candidate originally developed for HIV treatment, AZVUDINE (FNC), is a promising drug in the treatment of COVID-19, being able to reduce the patient's viral load leading to cure. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In another randomized clinical trial in moderate COVID‐19 patients, Azvudine shortened the time of NANC compared to the placebo group, accelerated virus elimination, and decreased the viral load significantly (trial number: NCT04668235). [ 35 ] No changes were observed for hepatic and renal functions between the FNC and control group, indicating the safety of Azvudine. Similarly, the adverse events of Azvudine were mainly related to the increase in ALT, GGT, AST, and GRADE 1 headache, with normalization of these events until the end of treatment.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another randomized clinical trial in moderate COVID‐19 patients, Azvudine shortened the time of NANC compared to the placebo group, accelerated virus elimination, and decreased the viral load significantly (trial number: NCT04668235). [ 35 ] No changes were observed for hepatic and renal functions between the FNC and control group, indicating the safety of Azvudine. Similarly, the adverse events of Azvudine were mainly related to the increase in ALT, GGT, AST, and GRADE 1 headache, with normalization of these events until the end of treatment.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Furthermore, Azvudine demonstrated efficacy against various virus variants, including Alpha, Beta, and Delta. [ 35 ] The patients receiving Azvudine (5 mg per person daily) did not experience increased risk. There were no statistically significant differences in adverse events between the Azvudine and placebo groups.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Patients with moderate COVID-19 were randomly assigned with a ratio of 1:1 to receive Azvudine 10 mg once a night plus standard treatment or placebo plus standard treatment. A total of 180 eligible patients with moderate COVID-19 were enrolled, of whom 172 completed the study ( Cabral et al, 2022 ). The results of both phase III clinical trials revealed that Azvudine significantly reduced the NANC time and viral load of the patients compared to the placebo group ( da Silva et al, 2023 ; Cabral et al, 2022 ).…”
Section: Four Phase III Clinical Trialsmentioning
confidence: 99%
“…A total of 180 eligible patients with moderate COVID-19 were enrolled, of whom 172 completed the study ( Cabral et al, 2022 ). The results of both phase III clinical trials revealed that Azvudine significantly reduced the NANC time and viral load of the patients compared to the placebo group ( da Silva et al, 2023 ; Cabral et al, 2022 ).…”
Section: Four Phase III Clinical Trialsmentioning
confidence: 99%
“…The results were detailedly disclosed in the preprints published on the Research Square platform (https://www.researchsquare.com), and showed that Azvudine significantly reduced the time of nucleic acid negative conversion (NANC) as well as the viral load of the patients compared to placebo. 4,5 Taken together, Azvudine could decrease the time of NANC, viral load, and median time to improvement in clinical condition, and increase the proportion of improvement in clinical condition on day 7 in the patients with COVID-19. In addition, Azvudine exhibited good safety and well tolerance as compared to placebo.…”
mentioning
confidence: 96%